400 Availability of Online Second Opinion Services for Spine Surgery: The Market Landscape. (April 2023) - Brown, Nolan James; Lien, Brian; Gattas, Sandra; Sahyouni, Ronald; Campos, Jessica; Zhang, Angie; Reardon, Taylor; Singh, Rohin; Gendreau, Julian; Oh, Michael
Abstract : INTRODUCTION: Second medical opinions may provide patients with a better understanding of their medical condition and empower them to make informed decisions about their health, particularly with respect to surgical treatments. However, the market landscape surrounding "online second opinion" services for spine surgery in the United States is not well-studied. METHODS: We utilized Google Trends (i.e., search data since 2010) to ascertain the level of interest in receiving second opinions for spinal surgery. In addition, we contacted the top 30 hospitals for neurology and neurosurgery in the U.S. News rankings by phone to obtain information regarding when/how and at what cost they provide second opinions for spine surgery. RESULTS: The cost of the second surgical opinions averaged $493 (±$343) USD (range $90–$1, 300); the time to receive a second opinion averaged 20 (±19) days (range 1 day–5 months). Remote or "online second opinion" programs charged an average of $643 (±$259) USD (range $100–$850), and the time to receive an "online second opinion" averaged 14 (±7) days (range 1–4 weeks). We found statistically significant increases in the relative interest for the search term "second medical opinion" over the past decade (P < 0.0001, t = 21.5201). ∼97% of hospitals (29/30) provided in-person consultations for patients seeking a second opinion from a spine surgeon. However, 63% (19/30) did not have remote options (phone/video call consultations or "online second opinions"), but provided in-person consultations as the sole choice. CONCLUSIONS: Although second opinions have been shown to be beneficial to patients, ambiguous or high costs and long wait times may serve as barriers for certain groups (i.e., uninsured or underinsured) and potentially diminish the quality of care.